2022
DOI: 10.1080/14459795.2022.2046843
|View full text |Cite
|
Sign up to set email alerts
|

Microtransaction spending and problematic gambling of UK university call of duty gamers

Abstract: Increased implementation of loot boxes within computer games has received widespread concern for the wellbeing of gamers, especially given the increased engagement during COVID-19 restrictions. Loot boxes share similarities with traditional gambling mechanisms that influence addiction-like behaviours and the amount of money spent on in-game items. The present study investigated loot box expenditure alongside peer engagement, perceptions of gaming value, self-worth, and problematic gambling behaviours of 130 Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The most frequently used standard has been typical or previous monthly spend. Alternatively, the RLI, a tool which measures risky or problematic engagement with loot boxes, has also been used in several studies [ 29 , 37 , 44 , 45 ]. While expenditure is a self-report measure of financial costs, the RLI is a conceptualization of ‘over-involvement’, capturing how people feel about their engagement—i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently used standard has been typical or previous monthly spend. Alternatively, the RLI, a tool which measures risky or problematic engagement with loot boxes, has also been used in several studies [ 29 , 37 , 44 , 45 ]. While expenditure is a self-report measure of financial costs, the RLI is a conceptualization of ‘over-involvement’, capturing how people feel about their engagement—i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Our primary outcome variable was not loot box expenditure, but instead the 'risky loot box index' (RLI). This has been used in several previous studies, shown to have significant relationships with both loot box purchasing and problematic gambling, and may represent a more direct measure of 'risky' or problematic engagement with loot boxes [29,37,[44][45][46].…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were found both with self-reported loot box spend and a validated measure of risky loot box engagement—the RLI [ 14 ]. This validated measure captures how gamers feel about their engagement, for example by asking them to rate their agreement with statements including ‘once I open a loot box, I often feel compelled to open another’—and has been used in several previous studies [ 14 , 16 , 20 , 21 ]. This measure therefore contrasts with self-reported loot box spend, in that it may be a more direct measure of risky behaviour.…”
Section: Introductionmentioning
confidence: 99%